Eco-friendly synthesis of silver and gold nanoparticles with enhanced antimicrobial, antioxidant, and catalytic activities - Vijayan, Remya; Joseph, Siby; Mathew, Beena (IET nanobiotechnology, 2018)
The present work is emphasised on the bio-fabrication of silver and gold nanoparticles in a single step by a microwave-assisted method using the leaf extract of Synedrella nodiflora as both reducing and stabilising agent. The synthesised nanoparticles are highly stable and show surface plasmon resonance peak at 413 and 535 nm, respectively, for silver and gold nanoparticles in UV–Vis spectrum. The functional group responsible for the reduction of metal ions were obtained from Fourier transform infrared spectroscopy. The crystalline nature of nanoparticles with face-centred cubic geometry was confirmed by the X-ray diffraction and selected area electron diffraction patterns. The morphology and sizes of the silver and gold nanoparticles were obtained from transmission electron microscopy images. The nanoparticles exhibit effective antimicrobial activities against various pathogenic strains. These antimicrobial properties were analysed by employing agar well diffusion method. The nanoparticles show significant antioxidant properties, and it was determined using 2, 2-diphenyl-1-picrylhydrazyl assay. The nanoparticles also show potent catalytic activity in the degradation of anthropogenic pollutant dyes Congo red and eosin Y by excess NaBH4. Thus, the current study demonstrates the potential use of S. nodiflora as a reducing and stabilising agent for the synthesis of silver and gold nanoparticles and their relevance in the field of biomedicine and catalysis.